Interfaith Marriage Registration: A Philosophical and Sociological Legal Review - Cindy Armelia Karunia; Nanik Sutarni; Ananda Megha Wiedhar Saputri (JURNAL AKTA, 2026)
This research aims to analyze the legal implications of a recent judicial policy concerning the registration of interfaith marriages from philosophical and sociological perspectives. The issue of interfaith marriage is among the most complex legal debates, as it intersects with positive law, religious norms, and human rights principles. The issuance of a judicial circular restricting the granting of interfaith marriage registration applications has generated significant controversy and raised questions regarding legal certainty, justice, and social effectiveness. The research method employed was normative legal research  utilizing statutory, conceptual, and case approaches. The statutory approach examined relevant legislation on marriage and population administration; the conceptual approach explored theories of legal certainty, justice, and legal utility; and the case approach analyzed judicial practices concerning interfaith marriage registration. The novelty  of this research lies in its integrated philosophical and sociological legal analysis of judicial policy, not merely assessing its juridical validity but also examining its broader social implications for civil rights protection and population administration. This research provides a multidimensional evaluation that connects normative conflicts with empirical societal realities. Based on the research, it concluded that the judicial policy is juridically problematic due to its inconsistency with higher-level legislation still in force. Philosophically, it reflects an overemphasis on formal legal certainty at the expense of justice and legal utility. Sociologically, it has proven ineffective in preventing interfaith marriages and may generate new administrative and civil rights complications. Therefore, comprehensive statutory regulation is required to ensure legal clarity, justice, and social protection.